Stilistika Linguistik dalam Cerpen Dilarang Menyanyi di Kamar Mandi Karya Seno Gumira Ajidarma - Dian, Dian Yunita Aryani (Signifiѐ, 2024)
The purpose of this study is to analyze the stylistics or style of language used by the author in composing his story into an interesting short story. The source of the data in this study is a short story entitled No Singing in the Bathroom by Seno Gumira Ajidarma. The method used is a qualitative approach. The results of this study can be explained that there are data that have been found both lexically, grammatically, and rhetorically. When viewed from the lexical elements, the most common aspect of word complexity is simple words that have denotative meanings. Whereas in the aspect of the type of words, verbal words are more dominant because this short story deals more with the activities that are happening. From the grammatical elements, there are types of phrases, clauses, and sentences that appear in the short story. Meanwhile, in the rhetorical element, several aspects were found, such as figurative language, elemental manipulation, and imagery.